Influence of the Lower Body on Seated Arm Cranking Performance - VanSumeren, Ashley L.; Bye, Thomas K.; Kilgas, Matthew A.; Hartvigsen, Matthew M.; Elmer, Steven J. (International Journal of Sports Medicine, 2018)
During upper-body tasks, use of the lower body is important for minimizing physiological strain and maximizing performance. The lower body has an integral role during standing upper-body tasks, however, it is less clear if it is also important during seated upper-body tasks. We determined the extent to which the lower body influenced seated arm cranking performance. Eleven males performed incremental (40+20 W·3 min−1) and short-duration maximal effort (5 s, 120 rpm) arm cranking trials with and without lower-body restriction. The lower body was restricted by securing the legs to the seat and suspending them off the floor. Upper-body peak oxygen consumption (V̇O2peak) and maximal power were determined. At the end of the incremental protocol, lower-body restriction reduced V̇O2peak by 14±12% (P<0.01) compared to normal arm cranking. At greater submaximal stages (60-100% isotime) heart rate, ventilation, RER, and arm-specific exertion increased to a greater extent (all P<0.05) with lower-body restriction. During short duration maximal arm cranking, lower-body restriction decreased maximal power by 23±9% (P<0.01). Results indicated that lower-body restriction limited aerobic capacity, increased physiological strain during high-intensity submaximal exercise, and compromised maximal power generating capacity. These results imply that use of the lower body is critical when performing seated arm cranking. Our findings have implications for exercise testing, training and rehabilitation.
Keywords: upper body; arm ergometry; leg restriction; oxygen consumption; muscular power